Body in Pain: the Case of Slavenka Drakulic - Milanko, Andrea (2011)
This paper deals with narrative procedures and their effect on the identity crisis in the first novel by Slavenka Drakulic, Holograms of Fear (1987). Drakulic's first-person narrator examines how the body responds to trauma before and after a surgical operation. Pain disintegrates the narrative voice, which only manages to tell a fragmented story. Narrative identity and body thus relate to one another in terms of a narrative voice that is trying to mediate between them. This autobiographical fiction both produces and questions thresholds of meaningful communication, the pain and words being its constitutive elements.